Transcranial direct current stimulation combined with speech therapy in Fragile X syndrome patients: a pilot study - Picciuca, Chiara; Assogna, Martina; Esposito, Romina; D’Acunto, Alessia; Ferraresi, Matteo; Picazio, Silvia; Borghi, Ilaria; Martino Cinnera, Alex; Bonnì, Sonia; Chiurazzi, Pietro; Koch, Giacomo (Frontiers in Neurology, 2023)
Background Fragile X syndrome (FXS) is the leading cause of genetic intellectual disability. Among the neurobehavioral dysfunctions in FXS individuals, language development and literacy are compromised. Recent evidence hypothesized that the disruption of excitatory glutamatergic and GABAergic inhibitory neurotransmission balance might be responsible for impairment in cognitive function. In this study, we evaluated for the first time, the safety, tolerability, and efficacy of anodal prefrontal transcranial direct current stimulation (tDCS) combined with standard speech therapy to enhance language function in FXS patients. Methods In total, 16 adult FXS patients were enrolled. Participants underwent 45 min of anodic tDCS combined with speech therapy for 5 weeks (3 times per week). Language function was evaluated using the Test for Reception of Grammar–Version 2 (TROG-2) and subtests of the Italian Language Examination (Esame del Linguaggio – II, EDL-II). Right and left dorsolateral prefrontal cortex transcranial magnetic stimulation and concurrent electroencephalography (TMS-EEG) recordings were collected at baseline and after the treatment to evaluate cortical reactivity and connectivity changes. Results After 5 weeks of combined therapy, we observed a significant improvement in the writing (7.5%), reading (20.3%), repetition (13.3%), and TROG-2 (10.2%) tests. Parallelly with clinical change, TMS-EEG results showed a significant difference in TMS-evoked potential amplitude over the left frontal cortex after treatment (−0.73 ± 0.87 μV) compared to baseline (0.18 ± 0.84 μV). Conclusion Our study provides novel evidence that left anodal prefrontal tDCS combined with standard speech therapy could be effective in enhancing language function in FXS patients, mainly by inducing a rebalance of the dysfunctional prefrontal cortical excitability.